The Influence of Social Media Use and Peer Association on the Morals of Grade XI Students at SMA Negeri 9 Gowa - Abdul Hamid Rusman; Muh. Rapi; Andi Maulana (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze and describe the influence of social media use (TikTok) and peer interaction on the moral development of eleventh-grade students at Gowa State Senior High School 9. The research method used was quantitative with an ex post facto approach. The population in this study amounted to 353 eleventh-grade students, with a research sample of 100 people obtained through proportional random sampling techniques. Data collection techniques used questionnaires, documentation, and observation. Data analysis used included descriptive analysis and inferential analysis through simple linear regression tests and multiple linear regression. The results showed that the use of TikTok social media partially had a significant negative effect on students' morals, while peer interaction had a significant positive effect. However, when tested together (simultaneously), the two variables made a very large contribution, reaching 97.6% in influencing variations in the quality of students' morals. This confirms that student behavior is highly dependent on how they interact in the digital world as well as the quality of their friendship environment at school. Keywords: Social Media, Peer Relationships, Student Morals.